2015
DOI: 10.1002/jcp.24883
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C Epsilon (PLCε) Induced TRPC6 Activation: A Common but Redundant Mechanism in Primary Podocytes

Abstract: In eukaryotic cells, activation of phospholipase C (PLC)-coupled membrane receptors by hormones leads to an increase in the intracellular Ca2+ concentration [Ca2+]i. Catalytic activity of PLCs results in the hydrolysis of phosphatidylinositol 4,5-bisphosphate to generate inositol 1,4,5-trisphosphate (IP3) and diacylglycerol (DAG) which opens DAG-sensitive classical transient receptor channels 3, 6, and 7 (TRPC3/6/7), initiating Ca2+ influx from the extracellular space. Patients with focal segmental glomerulosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 39 publications
(59 reference statements)
1
22
0
Order By: Relevance
“…PLCe1 was also shown to modulate adrenergic receptor-dependent cardiac contraction and to inhibit cardiac hypertrophy (22,23). Patients with focal segmental glomerulosclerosis have been found to have loss-of-function mutations in PLCe1, and PLCe1 itself interacts with transient receptor potential channel 6 (24)(25)(26)(27). Even more intriguing is the fact that a genome-wide association study identified the susceptibility loci for dengue shock syndrome at PLCe1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…PLCe1 was also shown to modulate adrenergic receptor-dependent cardiac contraction and to inhibit cardiac hypertrophy (22,23). Patients with focal segmental glomerulosclerosis have been found to have loss-of-function mutations in PLCe1, and PLCe1 itself interacts with transient receptor potential channel 6 (24)(25)(26)(27). Even more intriguing is the fact that a genome-wide association study identified the susceptibility loci for dengue shock syndrome at PLCe1 (28).…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment of podocytes was .95% as assessed by cell morphology, staining with an antipodocin antibody (Sigma-Aldrich) and by expression of nephrin, synapotopodin, and Wilms tumor protein (WT1), which is described in detail elsewhere. 57 Cell membrane capacity was used as another selection criterion for podocytes. Cell membrane capacity was estimated to be 71.262.3 pF (n=362) for primary podocytes; thus, there was no significant difference to conditionally immortalized murine podocytes, which had cell membrane capacities of 63.463.3 pF (n=52).…”
Section: Podocytes Used In the Studymentioning
confidence: 99%
“…OAG‐induced current densities in PASMCs were about 20‐fold higher than in podocytes, which only reached about 1 pA·pF −1 . Interestingly, few studies utilizing freshly isolated podocytes instead of the immortalized cell lines confirmed these very small current amplitudes upon stimulation with angiotensin II (Eckel et al ., ; Kalwa et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…TRPC6 channels are expressed in a variety of tissues and cell types, including vascular smooth muscle cells, mesangial cells and podocytes. Although the presence of TRPC6 in podocytes has been demonstrated by several groups, there is considerable variability concerning the abundance of the channel protein and the size of functional responses to TRPC6 channel activators (Anderson et al ., ; Abkhezr et al ., ; Kalwa et al ., ). As dysregulation of TRPC6 channel expression in podocytes can occur in response to various stimuli, TRPC6 channels may also play a seminal role in secondary forms of FSGS.…”
Section: Introductionmentioning
confidence: 97%